2014
DOI: 10.1245/s10434-014-3780-9
|View full text |Cite
|
Sign up to set email alerts
|

A Competing Risk Analysis of Cancer-Specific Mortality of Initial Treatment with Radical Prostatectomy versus Radiation Therapy in Clinically Localized High-Risk Prostate Cancer

Abstract: Initial treatment with RP versus RT was associated with a decreased risk of CSM in men with clinically localized high-risk PC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…A recent study by Lee et al included patients with high-risk localized PCa that was treated with RP ( N = 251) or RT plus neoadjuvant ADT (nADT) ( N = 125)25. Results showed that the 5-yr CSS was longer in patients treated with RP compared with the combined group (96.5% vs. 88.3%).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Lee et al included patients with high-risk localized PCa that was treated with RP ( N = 251) or RT plus neoadjuvant ADT (nADT) ( N = 125)25. Results showed that the 5-yr CSS was longer in patients treated with RP compared with the combined group (96.5% vs. 88.3%).…”
Section: Resultsmentioning
confidence: 99%
“…21 However, this finding was based on two small retrospective studies and the authors of the meta-analysis were concerned about the limited quality of most studies included in the meta-analysis. 22,23 In contrast, Boorjian et al reported similar 10-year cancer-specific survival in patients treated with RP or RT + ADT. 8 Overall, the retrospective data that compared outcomes of RP to RT + ADT suffered from selection bias, variable length of ADT use, and contamination of the RP cohort by adjuvant and salvage therapies.…”
Section: Discussionmentioning
confidence: 98%
“…[4][5][6][7] On the other hand, large retrospective studies with long followup times demonstrated equivalence of RP to RT + ADT. [8][9][10][21][22][23][24][25][26] A meta-analysis showed a modest improvement in cancer-specific survival with RP compared to RT + ADT. 21 However, this finding was based on two small retrospective studies and the authors of the meta-analysis were concerned about the limited quality of most studies included in the meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Due to insufficient power and small series (89 patients) no conclusion could be drawn about the efficacy. Nonetheless, some observational data suggest that outcomes with RP lead to better overall and cancer-specific survival than RT [108112]. Wallis and colleagues recently published a meta-analysis comparing RP with EBRT or BT [108].…”
Section: Rt Compared To Surgerymentioning
confidence: 99%